2004
DOI: 10.4049/jimmunol.173.2.1426
|View full text |Cite
|
Sign up to set email alerts
|

The Myelin-Associated Oligodendrocytic Basic Protein Region MOBP15–36 Encompasses the Immunodominant Major Encephalitogenic Epitope(s) for SJL/J Mice and Predicted Epitope(s) for Multiple Sclerosis-Associated HLA-DRB1*1501

Abstract: Autoimmune response to the myelin-associated oligodendrocytic basic protein (MOBP), a CNS-specific myelin constituent, was recently suggested to play a role in the pathogenesis of multiple sclerosis (MS). The pathogenic autoimmune response to MOBP and the associated pathology in the CNS have not yet been fully investigated. In this study, we have characterized the clinical manifestations, pathology, T cell epitope-specificity, and TCRs associated with experimental autoimmune encephalomyelitis (EAE) induced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 37 publications
0
50
0
Order By: Relevance
“…Northern blot analysis, in situ hybridization, immunochemistry, and immunoelectron microscopy (16,17) indicated that MOBP is expressed exclusively in CNS white matter and more particularly throughout compact myelin, predominantly at the major dense lines of myelin (16). The encephalitogenic potential of MOBP was demonstrated in H-2 b (18) and H-2 s (19,20) mice, and two separate studies of proliferative response to MOBP peptides (pMOBP) by PBL from MS patients and controls indicated that MOBP65-87 was the region most frequently recognized by MS patients T cells (18). Another study indicated that PBL obtained from relapsing/remitting MS patients mount a proliferative response to human MOBP, especially at aa 21-39 (21).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…Northern blot analysis, in situ hybridization, immunochemistry, and immunoelectron microscopy (16,17) indicated that MOBP is expressed exclusively in CNS white matter and more particularly throughout compact myelin, predominantly at the major dense lines of myelin (16). The encephalitogenic potential of MOBP was demonstrated in H-2 b (18) and H-2 s (19,20) mice, and two separate studies of proliferative response to MOBP peptides (pMOBP) by PBL from MS patients and controls indicated that MOBP65-87 was the region most frequently recognized by MS patients T cells (18). Another study indicated that PBL obtained from relapsing/remitting MS patients mount a proliferative response to human MOBP, especially at aa 21-39 (21).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…The binding ability of overlapping 9-aa segments of NF-M was estimated as the sum of scores for the four pockets. Previous calculations with this in-house computer program successfully predicted minimal core epitopes, all of which scored 25 or lower (46,54,55). Initial model structures of the I-A b peptide-binding domain in complex with 12-aa peptides that include the predicted core epitopes were constructed based on the experimental structure.…”
Section: Sequencing Of the Tcr Cdr3 Regions From T Cell Hybridomasmentioning
confidence: 99%
“…Chronically active plaques present demyelination and axonal injury, with reactive astrocytes and immunoglobulin deposition [137]. At a cellular and molecular level, several studies have showed that T cells from MS patients are able to recognize different myelin protein targets, including myelin basic protein (MBP) [138,139], proteolipid protein (PLP) [140], myelin oligodendrocyte glycoprotein (MOG) [141]and myelin-associated oligodendrocyte basic protein (MOBP) [142]. These patients also present auto-reactive CD8+ T cell [143].…”
Section: Depression and Multiple Sclerosismentioning
confidence: 99%